Tear Lactoferrin and Lysozyme as Clinically Relevant Biomarkers of Mucosal Immune Competence - Hanstock, Helen G.; Edwards, Jason P.; Walsh, Neil P. (Frontiers in Immunology, 2019)
Tears have attracted interest as a minimally-invasive biological fluid from which to assess biomarkers. Lactoferrin (Lf) and lysozyme (Lys) are abundant in the tear fluid and have antimicrobial properties. Since the eye is a portal for infection transmission, assessment of immune status at the ocular surface may be clinically relevant. Therefore, the aim of this series of studies was to investigate the tear fluid antimicrobial proteins (AMPs) Lf and Lys as biomarkers of mucosal immune status. To be considered biomarkers of interest, we would expect tear AMPs to respond to stressors known to perturb immunity but be robust to confounding variables, and to be lower in participants with heightened risk or incidence of illness. We investigated the relationship between tear AMPs and upper respiratory tract infection (URTI; study 1) as well as the response of tear AMPs to prolonged treadmill exercise (study 2) and dehydration (study 3). Study 1 was a prospective cohort study conducted during the common cold season whereas studies 2 and 3 used repeated-measures crossover designs. In study 1, tear Lys concentration (C) as well as tear AMP secretion rates (SRs) were lower in individuals who reported pathogen-confirmed URTI (n = 9) throughout the observation period than in healthy, pathogen-free controls (n = 17; Lys-C, P = 0.002, d = 0.85; Lys-SR, P < 0.001, d = 1.00; Lf-SR, P = 0.018, d = 0.66). Tear AMP secretion rates were also lower in contact lens wearers. In study 2, tear AMP SRs were 42-49% lower at 30 min - 1 h post-exercise versus pre-exercise (P < 0.001, d = 0.80-0.93). Finally, in study 3, tear AMPs were not influenced by dehydration, although tear AMP concentrations (but not secretion rates) displayed diurnal variation. We conclude that Lf and Lys have potential as biomarkers of mucosal immune competence; in particular, whether these markers are lower in infection-prone individuals warrants further investigation.